Noninvasive method for mapping CVR in moyamoya disease using ASL-MRI. Issue 6 (June 2015) - Noguchi, Tomoyuki; Kawashima, Masatou; Nishihara, Masashi; Egashira, Yoshiaki; Azama, Shinya; Irie, Hiroyuki
Highlights: A clinical use of a pulse-wave-synchronized ASL-MRI (pulsy ASL-MRI) was proposed. Resting IMP-SPECT correlated with pulsy ASL-MRI in moyamoya disease. ASL-MRI could measure cerebrovascular reserve noninvasively in moyamoya disease. Abstract: Purpose: To project a noninvasive method for mapping cerebrovascular reserve (CVR) in moyamoya disease (MMD) using ASL-MRI. Methods: 16 MMD patients underwent cerebral blood flow (CBF) examinations by standard ASL-MRI, pulse-wave-synchronized ASL-MRI (pulsy ASL-MRI) which tagged the arterial blood coincident with a peak of a pulse wave, and single photon emission computed tomography (SPECT) imagings with iodine-123-N-isopropyl-p-iodoamphetamine in the resting (rest-IMP) and after acetazolamide challenge (ACZ-IMP). Hemispheric 32-sided cerebral blood flow (CBF) values were measured with normalized CBF maps created from standard ASL-MRI (standard-ASL value), pulsy ASL-MRI (pulsy-ASL value), rest-IMP (rest-IMP value), and ACZ-IMP (ACZ-IMP value). CVR based on rest-IMP and ACZ-IMP values (IMP-CVR) was calculated. ASL-CVR was also calculated on the basis of corrected standard-ASL values and pulsy-ASL values, which were adjusted to the ACZ-IMP values and rest-IMP values, respectively, by the least-squares method. We assessed the relationships between rest-IMP values and pulsy-ASL values, ACZ-IMP values and standard-ASL values, and IMP-CVR and ASL-CVR. Results: Significant relationships were observed between rest-IMP values and pulsy-ASL values (correlation coefficient ( r  = 0.557, p  < 0.01)), ACZ-IMP values and standard-ASL values ( r  = 0.825, p  < 0.01), and IMP-CVR and ASL-CVR ( r  = 0.736, p  < 0.01). Conclusions: ASL-MRI is equivalent to SPECT and that it might serve as a noninvasive method for mapping CVR in MMD.